(untitled) - Seidensticker, Edward (Tokyo,New York, 1979)
These are a few of the titles that adorned a weekly column the author once wrote for a Tokyo newspaper, and a good selection of its short witty comments on Japan's cultural, political, and social life is includes in This country, Japan.
Keywords: Japanese literature; History and criticism